Measuring the readability of Indonesian biomass websites: The ease of understanding biomass energy information on websites in the Indonesian language. (June 2016) - Biddinika, Muhammad Kunta; Lestari, Retno Puji; Indrawan, Bayu; Yoshikawa, Kunio; Tokimatsu, Koji; Takahashi, Fumitake
Abstract: Renewable energy-related information in the Indonesian language ( Bahasa Indonesia ) is nowadays easily accessible on the internet and seeking information from the internet has become the second highest activity of Indonesian netizens. This paper aims to examine the readability of biomass energy-related information that is retrieved from the internet and available in the Indonesian language. By using Google® Indonesia׳s search results of four keywords on biomass renewable energy in the Indonesian language, educational materials on biomass energy were examined. Some inclusion and exclusion criteria have been applied among the search results in order to discriminate the educational materials among the results for further readability assessment by employing four readability standard formulas (SMOG, Gunning Fog, Flesch–Kincaid, and Dwiyanto Djoko Pranowo׳s). The results showed that information on biomass energy is still difficult to understand by the general public. The results may also become a success indicator of biomass energy campaigns as well as renewable energy education in Indonesia as a key role for its implementation in the near future. This study also contributes to the information quality assessment framework to languages other than English since internet technology has made information in any language accessible.